Modern Japan - Kerbo, Harold R.; McKinstry, John A. (Boston MA : McGraw-Hill, 1998)
The place, the people, and the past. Japanese culture and social structure. The Japanese political system. The Japanese economy. Social stratification in Japan. The Japanese power elite. The family. Religion. Education. Cities. Social problems in modern Japan. Social change and Japan in the twenty-first century.
Keywords: Japan; Japan